The role of residential colleges in nurturing professional ethics among university students: prospects and challenges - Awang Abd. Rahman @ Jusoh, Amilah; Awang, Abdul Bari (Eubios Ethics Institute, 2010)
Tertiary or university level is the highest level of education before a person embarking on his/her career life. The expectations have always been high towards university to mould studentsʼ good personalities. This is mainly to ensure that the graduates are capable of handling obstacles and challenges in their real life. In normal circumstances, the role of residential colleges in shaping students behavior is not much highlighted. This paper explores the potential role of residential colleges in a university especially in inculcating organizational behaviour among students. This study employs qualitative method mainly through library research and interview sessions with relevant parties who are directly involved in the administration of colleges at public universities. Several cases were studied, and the findings are used to illustrate and explain the actual scenario. The study found that residential colleges have many opportunities to educate students in the respect of professional ethics. Colleges provide favourable environment to appropriately inculcating balance in studentsʼ development including towards organizational behavior throughout their years of study. The efforts can be divided into two categories: On the level of inner self which can be further divided into awareness, self-reflection and conviction, and on the level of practicality. The students will value the spirit of mutual respect and social responsibility throughout their dealing with college office staff. These values, even though may be seen as simple, are indeed, invaluable and important for their future experience in the society. Several challenges to such role are also identified which can be divided into two aspects: Students and university.